Inhibitory Effort of MLN2238 on Basal-Like Breast Cancer: An Investigation Based on the Gene Set Enrichment Analysis: Effect of MLN2238 on Basal-Like Breast Cancer - Wang, Dapeng; Li, Yunyan; Luo, Fushen; Song, Xue; Wu, Shuang; Chen, Ying; Zhang, Na (Cellular and Molecular Biology, 2023)
Basal cell-like breast cancer (BLBC), one subtype of breast cancer, has the characteristics of a high recurrence rate and strong invasiveness. Therefore, it is necessary to exploit new drugs for the therapy of BLBC. The data on small molecular drugs were downloaded from the cancer drug sensitivity genomics (GDSC) database, and the target gene information of small molecular drugs was obtained from the SWISS website. Based on the TCGA database, a genome-wide t-value sequencing for screening differentially expressed genes (DEGs) was constructed. The bioinformatics analysis was further performed. The cell cycle was determined using flow cytometry. Western blot was performed to calculate the expression of P21 and P27. siPLK1 transfection was performed to interfere with PLK1 expression. And further cell experimental techniques were performed. The specific effect and mechanisms of the screened small molecular drugs were confirmed through clinical sample studies and in vitro experiments. MLN2238 could significantly inhibit the proliferation of HCC38, a BLBC cell line. The PPI network based on the target gene significantly up-regulated by MLN2238 shows that PLK1 is the key gene, and KEGG analysis shows that the up-regulated target gene is in the cell cycle. Flow cytometry showed that MLN2238 blocked HCC38 cells in the G2/M phase. The results of the Western blot revealed that MLN2238 inhibited the expression of P21 and P27 in HCC38 cells. The survival heat map based on the TCGA database shows that PLK1 has the greatest impact on the survival of breast cancer. Patients with high levels of PLK1 expression had a poorer overall survival rate than those with low levels of PLK1. Cell experiments in vitro revealed that the PLK1 expression decreased significantly after siPLK1 transfection. The ability of cell proliferation was significantly inhibited after SiPLK1 transfection. MLN2238 is a potential target drug for the therapy of BLBC, and PLK1 is the target gene for MLN2238 to inhibit BLBC.